Spejle i middelalderens og renæssancens Europa: Produktion, symbolik og arkæologiske levn - Esdahl-Schou, Vibe (Hikuin, 2010)
Mirrors in medieval and renaissance Europe Production, symbolism and archaeological remains By Vibe Esdahl-Schou Until only a few decades ago medieval glass mirrors were an almost unexplored subject in archaeology mostly because of a lack in finds. Lately a lot of attention has been drawn to the subject and the quantity of finds is growing rapidly. Through the Middle Ages convex glass mirrors fitted in a simple wooden frame were fairly common and can be seen in many paintings from the 15th and 16th century. Only a handful of wooden frames and cases are known from Denmark. Around 1500 A.D. the Venetian manufacture of plate glass mirrors was perfected and Venetian mirrors became extremely valuable luxury items reserved for princes or kings. The convex glass mirror was still preferred by the common people and remained popular until the 1800s when Industrialisation made it possible to produce plate glass en masse at a reasonable price.